Uruguay - Trade and Logistics : An Opportunity - Main Report - World Bank (World Bank, 2012)
Globalization has brought about a rapid expansion of international trade and a dramatic change in trade structure. The liberalization of trade in goods and services, containerization, new integrated transport networks, advances in information communication technology and modern business logistics have created unprecedented business opportunities for the trade and transport industries, as firms increasingly rely on global supply chains for production and distribution. In response to the government's request, this study assesses Uruguay's potential as a logistics hub and as a regional distribution center. The competitiveness of Uruguay's logistics system is assessed from an international perspective and policy recommendations towards further efficiency gains are provided. The study focuses on policies related to enhancing domestic and regional trade facilitation and assesses the wider economic impact of such reforms on logistics costs and trade.